Accident Detection and Smart Rescue with Real Time Location using Image Processing - Shaikh, Asadullah; Gangerdiwala, Zainab; Shaikh, Sarah; Kothari, Husain (International Journal of Computer Sciences and Engineering, 2019)
Accidental detection rescue system is an application intended for the use of providing assistance to the victim in case of emergency. The credibility and accessibility of this application is designed in accordance with the existing systems and improved with enhanced features and technology. With an application detecting the location of the accident and image processing classifying it as accidental or fake image the application is built to provide assistance to the end user in a systematic manner. The proposed system i.e. the Accident Detection and Rescue System (ADRS) consists of two phases; the detection phase which is used to detect type of accident based on the image captured and the notification phase, immediately after an accident has occurred, is used to send detailed information such as images, accident location, date and time of accident, etc to the emergency responder for fast recovery. ADRS will ensure that the victim of the accident is rescued within an hour of accident which is also known as Golden Hour. Malicious use of the application will be prohibited and it will be available to all users at any particular instance of time.